Portraying Migrant Families in Academic Publications: Naming and Framing - Juozeliūnienė, Irena; Bielevičiūtė, Indrė; Budginaitė-Mačkinė, Irma (Vilnius University Open Series, 2020)
In this chapter the authors set out to examine how migrant families are named and framed in academic publications by Lithuanian researchers published from 2004 to 2017, available in Lithuanian and international academic databases. The authors aim to disclose how Lithuanian academics perceive the change of family boundaries and fluidity of family relations in the context of global migration, and how the meanings of ‘change’ are used within academic publications that have sought to define the migrant family life as ‘troubling’. The analysis of publications presented in this chapter was carried out from January to March 2018. It formed a sub-study of the research project ‘Global Migration and Lithuanian Family: Family Practices, Circulation of Care, and Return Strategies’ (2017–2019), funded by the Lithuanian Research Council. The analysis has revealed that Lithuanian researchers portray migrant families as extended in space, liquid, networked, survived, but unsecure because of ongoing risks as well as experiencing ‘losses’ or/ and ‘gains’. The researchers conclude that portraits presented by the academics are framed by the family ideology, while naming of migrant families highly rely on the images of ‘how a family should be’.
Keywords: Migrant family; naming family; framing family; troubling family